Comparison of Pre and Post LASIK Corneal Thickness by Orbscan, Anterior Segment Optical Coherence Tomography, Specular Microscopy, Ultrasonic Pachymetry - Metu Rajput; Charu Tandon; Uma Sridhar (Delhi Journal of Ophthalmology)
Background : To measure corneal thickness by Orbscan, Anterior Segment Optical Coherence Tomography, Specular microscopy, Ultrasonic pachymetry Pre and Post LASIK and to compare the four techniques. Materials and Methods: A prospective study was conducted at a tertiary care eye hospital to compare corneal thickness by orbscan, anterior segment optical coherence tomography, specular microscopy, ultrasonic pachymetry pre and post LASIK in 50 subjects (100 eyes). Results: Baseline mean CCT measured with ORBSCAN was 556.73 ± 17.07, with ULTPACH was 544.13 ± 16.94, with SPEC was 544.55 ± 18.98 and with ASOCT was 544.61 ± 16.39. There was statistically significant difference in mean CCT among orbscan and the other three methods (P <0.001) preoperatively. On postoperative day 7, mean CCT measured with ORBSCAN was 456.60 ± 30.41, with ULTPACH was 475.02 ± 22.26, with SPEC was 472.06 ± 22.99, and with ASOCT was 475.75 ± 24.17. There was statistically significant difference in mean CCT among orbscan, and the other three techniques namely, ultrasonic pachymetry, specular microscopy, anterior segment optical coherence tomography on postoperative day 7 (p <0.001). On postoperative day 30, mean CCT measured with ORBSCAN was 459.32 ± 27.40, with ULTPACH was 480.95 ± 24.88, with SPEC was 475.31 ± 23.20, and with ASOCT was 479.12 ± 23.83. This also showed statistically significant difference in mean CCT between orbscan, and the other three methods.(P <0.001). Conclusion: Ultrasonic pachymetry is considered as the gold standard method of measuring CCT and it compares favourably with specular microscopy and AS OCT. Orbscan has a tendency to overestimate pre LASIK and underestimate post LASIK.